Capitalist exploitation and animal ethics in water for elephants: A Marxist and utilitarian perspective - Khoiriah, Umul Fajar; Haryanto, Sigit (NOTION: Journal of Linguistics, Literature, and Culture, 2025)
In early 2025, numerous cases of human rights violations in the circus industry emerged in Indonesia, bringing public attention to the exploitation of both workers and animals. This study explores the portrayal of exploitation in Francis Lawrence’s Water for Elephants through Karl Marx’s theory of labor exploitation combined with the animal ethics perspective of Singer and Regan, presenting an insightful dual perspective in film analysis. This qualitative research employs a literature study method, analyzing scenes, dialogues, and visual elements of the film. The findings reveal that Water for Elephants portrays various indicators of exploitation: hazardous work conditions, low wages, lack of healthcare access, abuse, and poor living conditions. These conditions reflect capitalist-driven oppression for profit maximization in circus environments. The study concludes that the movie serves as a critical commentary on the ethical implications of labor and animal rights violations, reinforcing the need for broader societal awareness and reform in the treatment of both humans and animals in entertainment sectors.